Предмет: Математика,
автор: лоджик
погите пж ,а то не как не пойму
Приложения:
Ответы
Автор ответа:
1
(-9,7+7,1)/(-1 3/17)=2,21
– 9,7 + 7,1 = – 2,6
-2,6:( - 1 3/17)=(- 2 6/10) ÷ (- 1 3/17) = ( - 13/5) ÷ ( - 20/17) = ( - 13/5) × ( - 17/20) = 221/100 = 2 21/100=2,21
(3 1/8 - 2 5/12)*(-1 3/17) = - 5/6
3 1/8 - 2 5/12 = 25/8 - 29/12 = (25 × 3 - 29 × 2)/24 = (75 - 58)/24 = 17/24
17/24 * (- 1 3/17) = 17/24 * ( - 20/17) = - 5/6
– 9,7 + 7,1 = – 2,6
-2,6:( - 1 3/17)=(- 2 6/10) ÷ (- 1 3/17) = ( - 13/5) ÷ ( - 20/17) = ( - 13/5) × ( - 17/20) = 221/100 = 2 21/100=2,21
(3 1/8 - 2 5/12)*(-1 3/17) = - 5/6
3 1/8 - 2 5/12 = 25/8 - 29/12 = (25 × 3 - 29 × 2)/24 = (75 - 58)/24 = 17/24
17/24 * (- 1 3/17) = 17/24 * ( - 20/17) = - 5/6
Автор ответа:
1
1пр
-9,7+7,1=-2,6
-2,6:(-1 3/17)=-2 3/5:-1 3/17=2 21/100=2,21
2пр
3 1/8-2 5/12=3 3/24-2 10/24=17/24
17/24*-1 3/17=-5/6
-9,7+7,1=-2,6
-2,6:(-1 3/17)=-2 3/5:-1 3/17=2 21/100=2,21
2пр
3 1/8-2 5/12=3 3/24-2 10/24=17/24
17/24*-1 3/17=-5/6
Похожие вопросы
Предмет: Русский язык,
автор: Деревянное1сердце
Предмет: Английский язык,
автор: donalexandr1
Предмет: Английский язык,
автор: TamerlanMMA
Предмет: Русский язык,
автор: rde2
Предмет: Математика,
автор: polinkamalinka33